Corporate Tax Cuts and the Decline in the Manufacturing Labor Share - Kaymak, Baris; Schott, Immo (Econometrica, 2023)
We document a strong empirical connection between corporate taxation and the manufacturing labor share, both in the US and across OECD countries. Our estimates associate 30 to 60% of the observed decline in labor shares with the fall in corporate taxation. Using an equilibrium model of an industry where firms differ in their capital intensities, we show that lower corporate tax rates reduce the labor share by raising the market share of capital‐intensive firms. The tax elasticity of the labor share depends on the joint distribution of labor intensities and value added at the micro level. Given the empirical distribution in the US manufacturing sector, our quantitative analysis suggests that corporate tax cuts explain a significant part of the decline in the manufacturing labor share since the 1950s. The shift away from traditionally large, labor‐intensive production units raised the concentration of market shares and reduced the concentration of employment.